“Piazza di Spagna, 26” by Cecília Meireles - Lopes, Delvanir [UNESP] (Associacao Internacional de Lusitanistas, 2024)
This article deals with a Cecilian text that until now had only been published in the periodical Diário de Notícias from Rio de Janeiro in 1955 a few years after the writer’s trip to Italy, together with her then husband Heitor Vinícius da Silveira Grillo (1902-1971). The text by Cecília Meireles, entitled “Piazza di Spagna, 26” contains a series of important references about the inhabitant of the address that gives the text its name: John Keats (1795-1821), writer of English Romanticism. On the stairs that lead to the Trinità dei Monti church, close to the Fontana della Barcaccia, the Rio writer traces, along with her feelings when she enters the house, episodes from the poet’s life and his works.
“Piazza di Spagna, 26”, de Cecília Meireles
Keywords: 26”; Cecília Meireles; Endymion; John Keats; Poemas Italianos; “Piazza di Spagna